Campyloneurum poloense (Polypodiaceae), a new combination and lectotypification for a Bolivian fern - Leon, Blanca (Phytotaxa, 2013)
During the revision of the fern genus Campyloneurum Presl (1836: 189) (Polypodiaceae) for Bolivia, a species previously described in Polypodium is recognized in the former, but requiring a new combination, which is done here, in addition to lectotypification and providing an updated description.